Pengaruh Tingkat Penjarangan Beri terhadap Kualitas Buah Anggur Kediri Kuning dan Prabu Bestari - SUKEWIJAYA, I MADE; GUNADI, I GUSTI ALIT; DHARMA, I PUTU; LANA, WAYAN (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022), 2022)
One of the problems encountered in cultivating grapes is the low quality of the fruit, the size of the fruit is still relatively small, the taste is not sweet, and the bunches are relatively compact. The problem of compactness or density of fruit bunches causes the shape, size, and maturity of the fruit in the bunch to be less uniform and there are some broken and decayed fruits. Thus, it is necessary to support cultivation technology to support the success of grape cultivation in order to increase the yield and quality of the fruit, one of which is through berry thinning activities. The purpose of this study was to determine the effect of berry thinning on the quality of the Kediri Kuning and Prabu Bestari grape varieties. The method used was a split plot design with the basic design of a randomized block design (RBD). The treatments tested were varieties and levels of fruit thinning. The first factor (main plot) was the variety consisting of Kediri Kuning (V1) and the Prabu Bestari variety (V2), while the second factor (sub-plot) was thinning level (P) with a level consisting of P0 = 0% control (without thinning). , P1 = fruit thinning 10%-25%, P2 = fruit thinning >25%-40%, P3 = fruit thinning 40%-55%. The results showed that thinning of berries in P3 treatment (>40-55%) gave a significantly higher effect on the variables of berry weight, berry diameter, fruit bunch length, fruit bunch weight, total dissolved solids, and vitamin C content.